Konstruksi Yuridis Hak Guna Bangunan di atas Hak Pengelolaan dalam Sistem Hukum Pertanahan - Anjas Setiawan (IPMHI Law Journal, 2025)
Land Management Rights (HPL) are a legal instrument that has developed in the practice of national land administration as a manifestation of the State's Sovereign Rights over land. However, their position in the structure of land rights is still a matter of debate, especially when Building Use Rights (HGB) are granted on top of them, which are widely used in the development of industrial, residential, and commercial areas. This issue is relevant because it concerns legal certainty and protection for rights holders and investors. This study aims to analyze the position of HPL in the land law system and construct the legal relationship between HPL holders and HGB holders. The method used is normative juridical legal research with a legislative and conceptual approach, through the analysis of primary, secondary, and tertiary legal materials. The results of the discussion show that HPL is not a property right as defined in the Basic Agrarian Law, but rather an administrative authority derived from the State's Right of Control, while HGB remains a land right granted by the state even though it is located within an HPL management area. Thus, the relationship between HPL holders and HGB holders is administrative-contractual in nature without changing the source of authority for granting HGB, so a conceptual clarification is needed to ensure legal certainty.